Sublingual immunization with the phosphate‐binding‐protein (PstS) reduces oral colonization by Streptococcus mutans. (2nd December 2015) - Ferreira, E.L.; Batista, M.T.; Cavalcante, R.C.M.; Pegos, V.R.; Passos, H.M.; Silva, D.A.; Balan, A.; Ferreira, L.C.S.; Ferreira, R.C.C.
Summary: Bacterial ATP‐binding cassette (ABC) transporters play a crucial role in the physiology and pathogenicity of different bacterial species. Components of ABC transporters have also been tested as target antigens for the development of vaccines against different bacterial species, such as those belonging to the Streptococcus genus. Streptococcus mutans is the etiological agent of dental caries, and previous studies have demonstrated that deletion of the gene encoding PstS, the substrate‐binding component of the phosphate uptake system (Pst), reduced the adherence of the bacteria to abiotic surfaces. In the current study, we generated a recombinant form of the S. mutans PstS protein (rPstS) with preserved structural features, and we evaluated the induction of antibody responses in mice after sublingual mucosal immunization with a formulation containing the recombinant protein and an adjuvant derived from the heat‐labile toxin from enterotoxigenic Escherichia coli strains. Mice immunized with rPstS exhibited systemic and secreted antibody responses, measured by the number of immunoglobulin A‐secreting cells in draining lymph nodes. Serum antibodies raised in mice immunized with rPstS interfered with the adhesion of bacteria to the oral cavity of naive mice challenged with S. mutans . Similarly, mice actively immunized with rPstS were partially protected from oral colonization after challenge with the S. mutans NG8 strain. Therefore, our results indicate that S. mutans PstS is a potential target antigen capable of inducing specific and protective antibody responses after sublingual administration. Overall, these observations raise interesting perspectives for the development of vaccines to prevent dental caries.